Problems In Implementing Inclusive Education at SDN Klampok 01, Brebes District - Fitri, Rila Melyana; Toharudin, Moh; Azalea, Dzikra Tsabita; Mawardah, Wafiq (International Journal of Education, Information Technology, and Others, 2025)
The purpose of implementing inclusive education in Indonesia is to provide educational facilities and services for children with special needs (ABK). Throughout Indonesia, inclusive education has been introduced in elementary schools. However, it has been shown that the implementation of inclusive education in Indonesia is related to a number of issues. The purpose of this study was to look at the various challenges faced by schools at SDN Klampok 01, Brebes District, Brebes Regency, and how inclusive education can be implemented. Data collection methods used in this study include observation and data analysis. Data from qualitative research then went through the process of data reduction, data presentation, and identification of conclusions. Based on the research findings, there are several issues in the implementation of inclusive education, including issues related to teachers, students, learning processes, school administration, lesson plans, facilities and infrastructure, and collaboration. The main problems found were the absence of special teachers to help ABK achieve their learning goals, the lack of facilities and infrastructure to support the goals and learning processes of ABK, the absence of resources that provide special services for ABK, and the existence of different types of ABK.